ANALYSIS OF THE INFLUENCE OF BACKHAND AND FOREHAND WELDING DIRECTIONS ON MECHANICAL PROPERTIES USING THE SMAW METHOD - Nolih; Santosa, Aa (Universitas Majalengka, 2023)
Abstract The use of metal materials to support human life continues to grow along with the rapid development of science and technology. This greatly influences the technology to process it into a ready-to-use product. Among the production techniques used to make a product is the welding process. Welding is a method of joining that is widely used in steel building construction and machine construction. Another connection method used on metal joints is bolts and rivets. Welding technology, besides being able to be used to join and cut metal, can also be used to fill holes in castings, make hard coatings on tools, thicken worn parts, and other kinds of repairs. AISI 1037 is a carbon steel with a carbon content of around 0.37%, which is classified as Medium Carbon Steel. The tensile strength of AISI 1037 is 650 MPa with a yield stress of 350 MPa. A test has been carried out on AISI 1037 with the welding method, where the welding method used is the 1G and 1 F welding process. With this method compared to the mechanical properties of the welding results, the seam used is seam V with an E 6013 electrode with a diameter of 2.6mm. The welding process refers to the AWS D1.1 standard with the SMAW welding type with a plate thickness of 5mm.